[Zr6O4(OH)4(benzene-1, 4-dicarboxylato)6]n: a hexagonal polymorph of UiO-66. Issue 42 (3rd May 2019) - Perfecto-Irigaray, Maite; Beobide, Garikoitz; Castillo, Oscar; da Silva, Ivan; García-Lojo, Daniel; Luque, Antonio; Mendia, Ander; Pérez-Yáñez, Sonia
Abstract : The first polymorph of the paradigmatic UiO-66 and the key conditions that led to its formation are reported. Abstract : Since its discovery in 2008, the paradigmatic UiO-66 has behaved as the germ that has prompted the chemistry of group-4 metal based metal–organic frameworks, all of them featuring outstanding thermal and chemical stability. Herein we present the first polymorph of UiO-66 and the key conditions that led to its formation.